2011
DOI: 10.1111/j.1463-1326.2011.01393.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficacy and tolerability of exenatide in combination with insulin in the Association of British Clinical Diabetologists nationwide exenatide audit*

Abstract: Addition of exenatide to obese, insulin-treated patients can improve glycaemia and weight. Adverse events were statistically but probably not clinically significantly higher, but combination treatment was less well tolerated. Overall, exenatide was less effective in lowering HbA1c among insulin-treated patients, although significant number of insulin-treated patients still achieved significant HbA1c, weight and insulin reductions. Further research into identifying obese, insulin-treated patients who will toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
2
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 23 publications
4
89
2
1
Order By: Relevance
“…Some previous studies, mostly observational, have investigated the effect of adding GLP-1 analogues to existing insulin treatment in patients with type 2 diabetes [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Our study differs from previous randomised controlled trials (RCTs) in that this is the first RCT where liraglutide was added to reverse weight gain in fairly well controlled patients, while all other trials added GLP-1 analogues to improve glycaemic control, and reported results on body weight as secondary outcomes, showing mixed results [16,17,19,23,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies, mostly observational, have investigated the effect of adding GLP-1 analogues to existing insulin treatment in patients with type 2 diabetes [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Our study differs from previous randomised controlled trials (RCTs) in that this is the first RCT where liraglutide was added to reverse weight gain in fairly well controlled patients, while all other trials added GLP-1 analogues to improve glycaemic control, and reported results on body weight as secondary outcomes, showing mixed results [16,17,19,23,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…However, GLP-1 analogues are expensive, have gastrointestinal side effects, and lack long-term safety and efficacy data, which renders it important to select those patients that are most likely to benefit from this therapy. Previous studies on the combination of GLP-1 analogues and insulin all focused on glycaemic benefit, with some reporting additional weight loss and others stable body weight [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Furthermore, most studies are either placebo controlled or observational and do not compare clinically relevant treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…However, in clinical trials examining GLP-1 receptor agonists in combination with sulphonylurea (with or without metformin) or insulin, the incidence of hypoglycemia, although low overall, was increased compared with placebo ( Table 6, in the Appendix) [32,33,42,[123][124][125][126][127][128][129][130][131][132][133][134][135]. Interestingly, the concomitant administration of GLP-1 receptor agonists with a sulphonylurea in the in situ perfused rat pancreas led to uncoupling of the insulinotropic effect of GLP-1 from its glucose dependence [136].…”
Section: Endocrine Effectsmentioning
confidence: 99%
“…There was a reduction of daily insulin dose of 42 + 2 Units (mean + SE) from a baseline of 120 + 99 Units (mean + SD), and 16.6% of patients discontinued insulin. 15 Herein we have assessed even more specific subgroups of patients in the audits; noting the glycaemic efficacy of exenatide and liraglutide as add-on therapies to one or two OADs as compared with add-on therapy to basal insulin (± OAD) or biphasic insulin (± OAD) at six months of treatment. Data have been adjusted for baseline HbA1c.…”
Section: The Use Of Exenatide or Liraglutide With Insulinmentioning
confidence: 99%